2022
DOI: 10.1055/s-0041-1740580
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Lacosamide in Lennox–Gastaut Syndrome: A Systematic Review and Meta-analysis

Abstract: Purpose Lennox–Gastaut syndrome (LGS) is one of the most difficult to treat childhood-onset epileptic encephalopathies. There is growing evidence that lacosamide is safe and efficacious in patients and adults with refractory epilepsy. However, the evidence regarding the efficacy of lacosamide in LGS is controversial so far. We aimed to evaluate the efficacy and tolerability of lacosamide in patients with LGS. Methods We conducted a systematic review on MEDLINE, EMBASE, COCHRANE CENTRAL, Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In line with this, another SLR conducted to assess the impact of LCM on mood in adult patients with epilepsy found that studies either reported a neutral or positive effect, including positive effects on depressive and anxiety symptoms [ 287 ]. A SLR in patients with DRE [ 288 ], and another specifically in patients with LGS [ 289 ], have noted that LCM can be associated with adverse mood and behavioural changes; however, AEs rarely led to discontinuations [ 288 ]. Of note, studies have suggested that LCM is effective and tolerable, with good retention rates in patients with epilepsy and intellectual disability [ 290 , 291 ]; a slower titration in the first 3 months of initiating LCM has been recommended to reduce PBAEs [ 290 ].…”
Section: Additional Asms Used In the Treatment Of Tscmentioning
confidence: 99%
“…In line with this, another SLR conducted to assess the impact of LCM on mood in adult patients with epilepsy found that studies either reported a neutral or positive effect, including positive effects on depressive and anxiety symptoms [ 287 ]. A SLR in patients with DRE [ 288 ], and another specifically in patients with LGS [ 289 ], have noted that LCM can be associated with adverse mood and behavioural changes; however, AEs rarely led to discontinuations [ 288 ]. Of note, studies have suggested that LCM is effective and tolerable, with good retention rates in patients with epilepsy and intellectual disability [ 290 , 291 ]; a slower titration in the first 3 months of initiating LCM has been recommended to reduce PBAEs [ 290 ].…”
Section: Additional Asms Used In the Treatment Of Tscmentioning
confidence: 99%
“…It is commonly administrated in patients with epilepsy and occasionally in patients with trigeminal neuralgia or other neuropathic pain [ 1 , 5 , 7 , 8 , 9 , 10 , 11 , 12 ]. A growing body of evidence demonstrated the effectiveness and tolerability of LCS in patients with epilepsy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Earlier reports have shown that this compound can decrease the frequency of interictal spikes as well as high-frequency oscillations in mesial temporal lobe epilepsy or refractory focal epilepsy [ 13 , 20 ].…”
Section: Introductionmentioning
confidence: 99%